A threshold gyroscope based on a bistable mechanism. (November 2019) - Tran, Hong Van; Ngo, Tien-Hoang; Chang, Pei-Lun; Chi, I-Ting; Tran, Ngoc Dang Khoa; Wang, Dung-An
Highlights: A threshold gyroschope based on a bistable mechanism is developed. An semi-analytical model is developed to investigate static and dynamic response of the device. A wireless signal detection scheme is devised for sensing of the angular rate threshold. Abstract: This paper describes a threshold gyroscope based on a bistable mechanism (BM). The device is capable of sensing one distinct signal when angular rate threshold is exceeded along one axis. This design minimizes the integrating scheme required by the analog gyroscope to obtain the threshold angular rate input. The automatic detection of the threshold value is achieved by the snap-through behavior of the BM and a wireless sensing scheme. A model is developed for efficient design of the device. Feasibility and effectiveness of the device is validated by experiments.